2008
DOI: 10.1001/archdermatol.2007.9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of IgE Autoantibody to BP180 With a Severe Form of Bullous Pemphigoid

Abstract: To determine the prevalence, immunoglobulin subclass distribution, and clinical correlation of antibodies (Abs), especially of IgE Abs, to BP180 and BP230 in patients with bullous pemphigoid (BP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
84
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 31 publications
7
84
2
5
Order By: Relevance
“…None of the 17 patients with IgG 4 as the only positive subclass had IgE antibodies against ADAMTS13, excluding a pathogenic role of IgE autoantibodies in TTP as described in, for example, bullous pemphigoid [14]. IgG subclasses (Fig.…”
Section: Subclass Distribution Of Igg Anti-adamts13 Antibodiesmentioning
confidence: 88%
“…None of the 17 patients with IgG 4 as the only positive subclass had IgE antibodies against ADAMTS13, excluding a pathogenic role of IgE autoantibodies in TTP as described in, for example, bullous pemphigoid [14]. IgG subclasses (Fig.…”
Section: Subclass Distribution Of Igg Anti-adamts13 Antibodiesmentioning
confidence: 88%
“…[102,106] In line, serum levels of anti-NC16A IgE significantly correlated with disease severity in individual BP patients. [96,99,106,107] These data are further supported by Delaporte et al and Kalowska et al, who found the disappearance of IgE anti-BP180 autoantibodies to be associated with clinical remission. [101,102] Interestingly, in two infants with BP, no IgE reactivity against the NC16A domain was detectable.…”
Section: Bp180-specific Ige Autoantibodiesmentioning
confidence: 90%
“…[79] The percentage of BP patients with IgE anti-BP180 NC16A autoantibodies varied substantially in the different reports. [46,83,95,96,[99][100][101][102][103][104][105][106] In the initial report, we identified anti-BP180 NC16A IgE reactivity in 55% of 18 BP sera. [96] Subsequent studies found IgE anti-NC16A in 100% of 10, 83% of 18, 22% of 37, 77% of 43, 30% of 67, 61% of 31, and 71% of 56 BP patients.…”
Section: Bp180-specific Ige Autoantibodiesmentioning
confidence: 99%
“…Eighty-five percent and 46% of BP sera contained IgG1 and IgG4 Abs against hCOL17, respectively (6). The presence of IgG1 autoantibodies has been associated with active BP phenotypes (5,6), and the autoantibody level has been correlated with the area of skin blistering (29). These clinical findings indicate that IgG1 might be the main pathogenic subclass in BP.…”
mentioning
confidence: 83%